Use of Tranexamic Acid during Total Endoprosthetic Replacement of the Hip Joint - D. D. Selivanov; V. A. Sungurov; V. V. Likhvantsev; D. Ye. Konev; L. A. Moiseikina (Общая реаниматология, 2010)
Objective: to evaluate the blood-saving activity, efficacy, and safety of tranexamic acid. Subjects and methods. Thirty-seven patients allocated into two groups were enrolled in the study of the efficacy of tranexamic acid as an agent in reducing blood loss during hip joint replacement. Group 2 patients were injected tranexamic acid, 10 mg/kg body weight, 20—30 minutes before and 3 hours after surgery in the same dosage. This resulted in a significant (48.5%) reduction in total blood loss (from 1089.6 to 560.8 ml) (p<0.05). No tranexamic acid-induced complications were found. The administration of tranexamic acid during total endoprosthetic replacement of the hip joint could reduce blood loss by 35 and 59.4% in the intraoperative and postoperative periods, respectively, and total blood loss by 48.4%. The use of tranexamic acid allows one to refuse transfusion of blood components during total endoprosthetic replacement of the hip joint. Key words: hip joint replacement, blood loss, tranexamic acid.